An Explanation for the Nitrous Oxide Layer Observed in the Mesopause Region. Issue 15 (8th August 2018) - Kelly, C. W.; Chipperfield, M. P.; Plane, J. M. C.; Feng, W.; Sheese, P. E.; Walker, K. A.; Boone, C. D.
Abstract: Recent satellite measurements of a layer of enhanced nitrous oxide (N2 O) in the mesosphere‐lower thermosphere (MLT) from the Atmospheric Chemistry Experiment‐Fourier Transform Spectrometer have suggested an unexpected, minor high‐altitude production source. Here we report the development of a mechanism and the first model simulations, which can explain the formation of this MLT N2 O layer. N2 O production occurs primarily via a reaction route involving the excitation of N2 from secondary electrons. Simulations using the Whole Atmosphere Community Climate Model, with external forcing from the Global Airglow model, quantitatively reproduce the observed vertical, latitudinal, and seasonal N2 O variations. Sensitivity results indicate that photoelectrons are far more important than previously predicted, causing approximately two thirds of global N2 O production in the MLT. Energetic electron precipitation over high latitudes provides the remaining contribution. Solar cycle analysis reveals N2 O enhancements of up to ×2 at solar maximum compared to solar minimum. Plain Language Summary: Nitrous oxide (N2 O) is an important gas in the Earth's atmosphere as it is a greenhouse gas and leads to the production of other nitrogen species that can deplete the ozone layer. It was previously assumed to only be produced at the Earth's surface, primarily through bacterial processes in soil. However, a minor upper atmospheric source has recently been identified from satellite observations. The key aim of this study is to find a plausible mechanism for the source of the observed N2 O based on current knowledge. We compare chemistry‐climate model simulations including likely chemical reactions and mechanisms to the satellite measurements. The model matches the observed spatial and seasonal N2 O variations. We also compare simulations with some of the N2 O production processes switched off. These results indicate that N2 O is constantly made through a chemical process involving the arrival of electrons trapped by the Earth's magnetic field near the poles, and light from the Sun at all latitudes. It should be emphasized that the concentration of N2 O in the upper atmosphere is extremely small compared to the concentration of N2 O in the lower atmosphere. Key Points: New parameterization to explain unexpected observations of N2 O in the mesosphere‐lower thermosphere (MLT) based on secondary electrons Model simulations reproduce spatial and seasonal N2 O variations from recent satellite observations providing quantitative support Photoelectrons are principal source for MLT N2 O production outside of high latitudes where energetic electron precipitation dominates